Significance and usefulness of imaging characteristics of gubernaculum tracts for the diagnosis of odontogenic tumors or cysts - Oda, Masafumi (PLoS One, 2018)
We aimed to determine the significance and usefulness of imaging characteristics of gubernaculum tracts (GT) for the diagnosis of odontogenic tumors or cysts. This was a retrospective analysis of relationships between odontogenic or non-odontogenic tumors or cysts and the GT that were visualized using multi-detector computed tomography (MDCT). The relationship between the size of a mass and expansion of the GT in all odontogenic tumors or cysts to which GTs were contiguous on MDCT, was statistically analyzed. Intact or expanded GTs were detected in MDCT images on the top of almost all odontogenic tumors or cysts, but not on non-odontogenic tumors or cysts. Characteristic image findings regarding the relationship between the GT and the odontogenic mass were detected for the respective odontogenic tumors or cysts in which the GTs were contiguous to the mass on MDCT. In ameloblastomas, expansion of the GTs significantly and very strongly correlated with tumor size (r = 0.741, p = 0.0001), but this correlation was very weak in dentigerous cysts (r = 0.167, p = 0.028) and there was no correlation between these parameters in odontogenic keratocysts (r = -0.089, p = 0.557). The imaging characteristics of GTs at the top of masses should be very useful for both the differential diagnosis of the pathological diagnosis of odontogenic masses and for differentiation between odontogenic and non-odontogenic masses.